Expanding Research on Corporate Corruption, Management, and Organizations. (July 2017) - Zyglidopoulos, Stelios; Hirsch, Paul; Martin de Holan, Pablo; Phillips, Nelson
In this special issue introduction, we briefly describe a variety of research paths researchers have followed to study the multifaceted phenomenon of corruption. Furthermore, we classify the papers included in this special issue according to their contribution to these research paths and briefly preview them. Finally, drawing on these four research paths and the papers included in this special issue, we propose a six-item agenda for future research on corruption.